2020
DOI: 10.1177/2332858420961110
|View full text |Cite
|
Sign up to set email alerts
|

Education Through TIME: Representations of U.S. Education on TIME Magazine Covers

Abstract: This study examined how TIME Magazine has visually represented and communicated ideas about education from TIME Magazine’s inception in 1923 through 2019. Drawing on theories of visual culture and social semiotic approaches to multimodality, the researchers conducted a qualitative multimodal content analysis of 115 covers that featured content related to education and schooling. The findings included (a) names and places are used to suggest authority, power, or relevance in education circles; (b) learning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A group of researchers studied how Time magazine covers communicated ideas concerning education throughout almost a century, from 1923 till 2019 (Kachorsky et al, 2020). The researchers did not examine the published articles, their aim was to explore the visual representation of education in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A group of researchers studied how Time magazine covers communicated ideas concerning education throughout almost a century, from 1923 till 2019 (Kachorsky et al, 2020). The researchers did not examine the published articles, their aim was to explore the visual representation of education in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding showed that the distinction between education and schooling evident to scholars is very vague and uncertain for journalists and the audience. Summing up, the researchers identified five categories among which four are of interest to the present research: learning and schooling presented as having not changed over time; overgeneralized and metonymic representations can stand for broad categories of education stakeholders; schools are presented as in need of fixing; and schools are perceived as sites for larger, sociopolitical debates (Kachorsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…perceptions’ (Weiss, 2020: 165) of issues and events. The Economist enjoys significant global presence and circulation figures (Holmes, 2020) whereas the liberal and left leaning Time magazine sets public discourses agenda (Weiss and Sternadori, 2020) and ‘is historically the most influential and most widely read publication’ in the US (Kachorsky et al, 2020: 2). On the other hand, Bloomberg Businessweek is a leading player in the North American business magazine market with a ‘strong international profile’ (Power et al, 2020: 6) evidenced in its circulation figures of 980, 000 weekly in 2017 (Bloomberg, 2017).…”
Section: Research Methods and Analytic Frameworkmentioning
confidence: 99%